Iš lietuviškų paveikslėlių knygų istorijos (1900-1930) - Korsakaitė, Ingrida (Knygotyra, 1996)
The present article is concerned with Lithuanian picture books from the period 1900 to 1930. A new term paveikslėlių knyga to specify this children's book genre has been introduced, which was not in wide use in Lithuanian book research before.In the late 19th century, picture books became popular in many countries such as Germany, England, and France. However, in Lithuania, due to extraordinary circumstances—namely, all publications in the Lithuanian alphabet being banned by the czarist government of the Russian Empire—there were very few children's books in circulation, and the art of book illustration could hardly be developed. The first Lithuanian picture books were published in some series (retold fairy tales, adaptations of classical literature, and instructive or didactic publications) by J. Zavadzki's printing house in 1909-1911 in Vilnius. They were illustrated with color lithographs brought from Germany (some of them could be from Poland), and the authors of these illustrations were unknown. From the end of the 19th century, the spread of illustrations in cheap mass production German picture books is characteristic of other East European countries as well (for example, Latvia and Poland).One very simple picture book written and illustrated by Lithuanian authors—P. Mašiotas and P. Kalpokas—appeared in 1913 in Riga.New opportunities for publishing children's books emerged when the Independent Republic of Lithuania was established. At first, in the early twenties, Lithuanian picture books again repeated the German editions. While Lithuania's printing technology was poor, many editions were set up and published in Germany. In the twenties, the company Kultūra made a significant contribution to the development of Lithuanian artists' picture books. This company established contacts with corresponding publishing houses in Munich, Mainz, and Leipzig, and published picture books with German artists’ (W. Bush, E. Osswald) illustrations. The company Kultūra published the Lithuanian fairy tale Eglė, žalčių karalienė (Eglė, the Queen of Grass Snakes) (Šiauliai, 1924), illustrated by Lithuanian painter K. Simėnas and printed in Leipzig. This large-format picture book is the very first Lithuanian fairy tale edition with color illustrations. Some artists' picture books were published in Germany in 1923 by the short-lived publishing firm Mala. Poet K. Binkis assisted with the translation. Mažylis karaliukas (The Little Prince) (Kaunas, 1923) by F. Ostyn, illustrated by H. Pellar, is distinguished for its high quality of color printing and artistic value. A very popular book was the Lithuanian edition of Struwwelpeter (Vaikai vanagai. Linksmos pasakos ir paveikslėliai, 1928) by H. Hoffmann, also translated by K. Binkis. The A. Ptašekas bookshop in Kaunas published especially many picture books during the period between the two world wars, but most of them featured imported German illustrations. The domestically illustrated Lithuanian picture books were increasingly published only in the thirties.The analysis of Lithuanian picture books shows that their development was not isolated from the books of the same genre published in other countries (especially in Germany) but involved many possible contacts with foreign publishing houses that had greater experience. Thus, they were able to gain general peculiarities of the genre and find their own way.